Necrotizing Fasciitis of the Breast: Case Report with Literature Review - Basem ALShareef; Nourah ALSaleh (Case Reports in Surgery)
Necrotizing fasciitis is a life-threatening aggressive soft tissue infection which usually affects the extremities, abdominal wall, or perineum. Breasts are rarely affected, with most cases presenting after trauma or surgical intervention. It may be misdiagnosed as abscess or cellulitis, leading to treatment delays. Here, we report a case of necrotizing fasciitis affecting both breasts in a 60-year-old female. Treatment included core biopsy managed with intravenous antibiotic and surgical debridement followed by a simple mastectomy. Currently, the patient is disease-free with a completely healed wound.